Panen Pertanian KWT Belimbing Parung Serab, Ciledug, Tangerang - Pangestu, Oktami (PT Literasi Nusantara Publisher, 2023)
KWT is a self-help group that grows from, by, and to the community. The group of farm women served as the medium of teaching for each member to enhance knowledge, skill and attitude to grow and develop into independent farm enterprises through use and access to existing sources of information and technology. A group of farm women (KWT) is one of the containers for female farmers, KWT differs from other farm groups, in its development KWT is directed to have a productive effort on a domestic scale that USES or processes on both agricultural and fisheries products. KWT belimbing is the association not only asa place to gather but also asa tool for learning and also asa reasoning member for addressing problems in the agriculture sector. Up to now, more than 10 registered housewives in hj umar gang area, the shaab parung have become members of KWT belimbing. With many members in KWT this proves that housewives in kwasan not only focus on her work asa housewife but also participate in other beneficial activities.